Russia – Guinea: Historical Aspects of Scientific Cooperation in the Fight against Dangerous Infectious Diseases - A. Yu. Popova; V. Yu. Smolensky; E. V. Naidenova; S. A. Shcherbakova; V. A. Safronov; E. V. Kolomoets; Ya. Yu. Itskov; V. Konomou; S. Boumbaly; M. N'Faly; M. Y. Boiro; M. S. Traore; et al. (Проблемы особо опасных инфекций)
The review presents the main results of scientific and technical cooperation between the Russian Federation and the Republic of Guinea over 10 years of joint work, since the deployment of a group of Russian specialists and mobile laboratories from the mobile complex of the specialized anti-epidemic team of the Rospotrebnadzor in August 2014 to provide practical and methodological assistance in eliminating the epidemic caused by the Ebola virus. The main areas of cooperation are the strengthening of laboratory and hospital facilities, joint research and training of specialists from specialized institutions in Guinea on biosafety issues. During the implementation of the Russian Federation programs of assistance to the Republic of Guinea in combating infectious diseases, public-private partnership mechanisms with UC “RUSAL” were involved, which made it possible to bring Russia’s participation in eradicating the epidemic of Ebola virus disease and subsequently strengthening Guinea’s national capacity to combat biological threats to the maximum effect.